2014
DOI: 10.1021/jp5040954
|View full text |Cite
|
Sign up to set email alerts
|

Activity and Architecture of Pyroglutamate-Modified Amyloid-β (AβpE3-42) Pores

Abstract: Among the family of Aβ peptides, pyroglutamate-modified Aβ (AβpE) peptides are particularly associated with cytotoxicity in Alzheimer’s disease (AD). They represent the dominant fraction of Aβ oligomers in the brains of AD patients, but their accumulation in the brains of elderly individuals with normal cognition is significantly lower. Accumulation of AβpE plaques precedes the formation of plaques of full-length Aβ (Aβ1-40/42). Most of these properties appear to be associated with the higher hydrophobicity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
85
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(93 citation statements)
references
References 67 publications
(88 reference statements)
8
85
0
Order By: Relevance
“…Additionally, we found that that the neuronal membrane damage caused by A␤3pE-42 results in a functional loss of plasma membrane integrity. These findings are consistent with recent publications demonstrating the capacity for A␤3pE-42 to form membrane-disrupting pores in synthetic lipid bilayers (22,23). Similarly, previous studies have shown that pE-A␤ oligomers disrupt lysosome membrane integrity in cultured neurons (50) and cause lactate dehydrogenase leakage from cultured astrocytes (49).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Additionally, we found that that the neuronal membrane damage caused by A␤3pE-42 results in a functional loss of plasma membrane integrity. These findings are consistent with recent publications demonstrating the capacity for A␤3pE-42 to form membrane-disrupting pores in synthetic lipid bilayers (22,23). Similarly, previous studies have shown that pE-A␤ oligomers disrupt lysosome membrane integrity in cultured neurons (50) and cause lactate dehydrogenase leakage from cultured astrocytes (49).…”
Section: Discussionsupporting
confidence: 92%
“…Neurons-Recent reports of pE-A␤ interactions with synthetic lipid membranes have suggested that pE-A␤ neurotoxicity is exerted via formation of ion-permeable membrane pores (22,23). We compared the capacity of A␤(1-42) and A␤3pE-42 to alter cellular ion homeostasis by measuring Ca 2ϩ flux in cortical neurons immediately following application of freshly prepared A␤.…”
Section: A␤3pe-42 Induces Rapid Ca 2ϩ Influx In Primary Corticalmentioning
confidence: 99%
See 1 more Smart Citation
“…Two types of zwitterionic lipid bilayers, containing DPPC and DOPC, and an anionic lipid bilayer containing DOPC/DOPS (mole ratio 4:1) were used in the simulations. Similar anionic lipid bilayers have been extensively simulated (33)(34)(35)(36)(37)(38)(39)(40)(41)(42). For each combination of two HVR peptides with three types of lipid bilayers, six independent simulations labeled HP1 to HP6 were performed.…”
Section: Methodsmentioning
confidence: 99%
“…The AFM images revealed that the amyloid channels exhibited various shapes from rectangular with four subunits to octahedral with eight. The heterogeneity in the Aβ channel conformations was further confirmed by recent extensive molecular dynamics (MD) simulations [30][31][32][33][34][35][36][37][38][39][40][41][42]. These showed that Aβ channels consisted of β-sheet-rich subunits with morphologies and dimensions in good agreement with the imaged AFM channels [12,29].…”
Section: Introductionmentioning
confidence: 61%